Vestibular migraine. (March 2015) - Stolte, Benjamin; Holle, Dagny; Naegel, Steffen; Diener, Hans-Christoph; Obermann, Mark
Background: The combination of vertigo, dizziness and balance disturbance with migraine is called vestibular migraine. Although it is estimated that up to 1% of the population suffers from this disease, it is still widely unknown and often underdiagnosed. Recently, the International Headache Society and the Báràny Society published the first joint document with mutually accepted diagnostic criteria for vestibular migraine. Method: This review summarizes current knowledge on vestibular migraine with regard to epidemiology, clinical presentation, pathophysiology, differential diagnosis and therapeutic options. Results: Approximately 30–50% of patients with migraine report vertigo, dizziness or balance disturbances with at least one migraine attack. Vestibular migraine often appears in a temporal delay to the first onset of migraine headache. In some patients the symptom of sudden onset disequilibrium was the main complaint and more worrisome than the accompanying migraine headache. The duration of attacks varies from a few seconds up to few days. The underlying pathophysiology of vestibular migraine is still widely unknown. As an important differential diagnosis, Ménière's disease has to be considered and excluded. Conclusion: As randomized controlled treatment trials are still missing in vestibular migraine, the therapeutic recommendations for vestibular migraine are currently based on the guidelines of migraine.